Mast cell leukemia: a rare case report and literature review - Tian, Lu; Yan, Xiang; Tian, Shaodan; Shen, Yang; Fan, Qiuyue (Frontiers in Oncology, 2025)
Mast cell leukemia (MCL) is an extremely rare and aggressive hematologic malignancy, characterized by a poor prognosis and short survival. Currently, no standardized treatment guidelines have been established. This study presents the clinical data of a patient with primary MCL accompanied by C-findings, and analyzes the clinical features, diagnostic challenges, and therapeutic approaches for this disease through a comprehensive review of the relevant literature. Furthermore, the study discusses current perspectives on research developments in MCL. By increasing clinical awareness of MCL, this work aims to provide valuable insights and references for clinicians in the diagnosis and management of this challenging condition.